2006
DOI: 10.1097/01.fpc.0000230413.97596.fa
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus genetic interactions and response to efavirenz-containing regimens: an Adult AIDS Clinical Trials Group study

Abstract: Multilocus genetic interactions between variant drug metabolism and transporter genes may predict efavirenz pharmacokinetics and treatment responses. This finding may have implications for better individualizing antiretroviral therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…With respect to the CYP3A5 and CYP3A4 SNPs, their influence on EFV CL/F was not significant, a result that is consistent with previous studies (16,35,51,56,57), suggesting that these isoenzymes play a minor role in EFV metabolism. Only Arab-Alameddine et al (1) found that the SNP 17163G3T of CYP3A4 influenced CL/F, but again this effect was observed only in patients with impaired CYP2B6.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…With respect to the CYP3A5 and CYP3A4 SNPs, their influence on EFV CL/F was not significant, a result that is consistent with previous studies (16,35,51,56,57), suggesting that these isoenzymes play a minor role in EFV metabolism. Only Arab-Alameddine et al (1) found that the SNP 17163G3T of CYP3A4 influenced CL/F, but again this effect was observed only in patients with impaired CYP2B6.…”
Section: Discussionsupporting
confidence: 78%
“…Cytochrome CYP2B6 is the main enzyme responsible for hydroxylation (60), with the partial involvement of CYP3A4/ CYP3A5 and, according to recent studies, CYP2A6 (1,15,31,32). In addition, several other CYPs, including CYP2D6, CYP2C9, CYP2C19, and CYP2C8, may also contribute, although their individual roles in EFV metabolism are not clearly defined (1,16,22,35,50,57). Genetic polymorphisms in these enzymes could change their activity, and this might explain a large part of the high interindividual PK variability of EFV.…”
mentioning
confidence: 99%
“…A recent larger study in adults by Haas et al also showed no correlation between the presence of CYP2B6-G516T polymorphisms and long-term virologic or immunologic response for up to three years [17]. Another study by Motsinger et al reported that virologic failure in patients receiving EFV was associated with a two-locus interaction between ABCB1-G2677T and CYP2B6-G516T [54]. Our previous data in 72 children who received EFV as a component of HAART [21] did not demonstrate differences in immunologic or virologic outcomes when analyzed in association with CYP2B6-G516T gene polymorphisms despite significant differences in EFV oral clearance.…”
Section: Impact Of Genetic Variants On Clinical Responsesmentioning
confidence: 94%
“…In addition, an inverse correlation between NVP intracellular concentrations and Pglycoprotein expression in PBMC has been reported [58], while another study demonstrated no association between EFV intracellular conc entrations and P-glycoprotein expression in PBMC [56]. Recent data have suggested that the genetic polymorphisms for ABCB1-G2677T (rs2032582), which is highly associated with the ABCB1-C3435T genotype, influence the virologic outcome combined with the CYP2B6-G516T genotype in patients who receive EFV containing HAART regimens [54]. In total, these data suggest that EFV, NVP, or their metabolites may be a substrate of P-glycoprotein.…”
Section: Impact Of the Abcb1 Genotype On Nnrti Pharmacokinetics And Cmentioning
confidence: 99%
See 1 more Smart Citation